Behavioural simulation of 2nd order Sigma Delta modulator - Hasim H.F.; Nadzri N.N.; Hamid F.A. (2023)
In this paper, the case study will be Sigma Delta ADC that will simulated in behavioural level using MATLAB SIMULINK to analyze the performance and the parameters that affect the performance. Sigma Delta ADC is the most commonly used ADC due to its advantage of trading off the speed with resolution at high sampling rate. High resolution ADC provide higher accuracy of data, converts from analogue to digital. With Sigma Delta ADC as oversampling converter, the performance will be evaluated using SNR, SFDR and SNR without INL and DNL influencing the ADC performances. 2009 IEEE.